Effects of ACL Reconstructive Surgery on Temporal Variations of Cytokine Levels in Synovial Fluid - Marco Bigoni; Marco Turati; Marta Gandolla; Paola Sacerdote; Massimiliano Piatti; Alberto Castelnuovo; Silvia Franchi; Massimo Gorla; Daniele Munegato; Diego Gaddi; Alessandra Pedrocchi; Robert J. Omeljaniuk; et al. (Hindawi Limited, 2016)
Anterior cruciate ligament (ACL) reconstruction restores knee stability but does not reduce the incidence of posttraumatic osteoarthritis induced by inflammatory cytokines. The aim of this research was to longitudinally measure IL-1β, IL-6, IL-8, IL-10, and TNF-α levels in patients subjected to ACL reconstruction using bone-patellar tendon-bone graft. Synovial fluid was collected within 24-72 hours of ACL rupture (acute), 1 month after injury immediately prior to surgery (presurgery), and 1 month thereafter (postsurgery). For comparison, a "control" group consisted of individuals presenting chronic ACL tears. Our results indicate that levels of IL-6, IL-8, and IL-10 vary significantly over time in reconstruction patients. In the acute phase, the levels of these cytokines in reconstruction patients were significantly greater than those in controls. In the presurgery phase, cytokine levels in reconstruction patients were reduced and comparable with those in controls. Finally, cytokine levels increased again with respect to control group in the postsurgery phase. The levels of IL-1β and TNF-α showed no temporal variation. Our data show that the history of an ACL injury, including trauma and reconstruction, has a significant impact on levels of IL-6, IL-8, and IL-10 in synovial fluid but does not affect levels of TNF-α and IL-1β.